Changes in blood center red blood cell distributions in the era of patient blood management: the trends for collection (TFC) study. Issue 8 (24th June 2016) - Yazer, Mark H.; Jackson, Bryon; Beckman, Neil; Chesneau, Stuart; Bowler, Patrick; Delaney, Meghan; Devine, Dana; Field, Stephen; Germain, Marc; Murphy, Mike F.; Sayers, Merlyn; Shaz, Beth; et al.
Abstract : BACKGROUND: As patient blood management becomes more widespread, fewer red blood cell (RBC) units have been transfused. This multinational study evaluated changes in blood center RBC distributions. STUDY DESIGN AND METHODS: Data on number and ABO and D groups of RBC distributions were obtained from several large American blood centers and national or provincial blood services (NPBS) from fiscal year (FY) 2010 through FY2014. Due to relatively larger numbers of distributions and differences in ABO and D groups between the Japanese Red Cross and the other NPBS, Japanese data were not included in distributions calculations. RESULTS: Data from seven American blood centers and eight NPBS were obtained. Overall, at both the American and the seven NPBS that were analyzed, there were declines in the number of RBC distributions between FY2010 and FY2014, 16.9 and 8.0%, respectively. The number of O– RBC distributions decreased by 9.0% at American blood centers but the proportion of RBC distributions that were O– increased by 9.3% during this time. The NPBS had 1.6% increase in O– RBC distributions and 10.5% increase in the proportion of O– distributions. The proportion of O+ distributions increased slightly over time at American centers (2.9%) while decreasing slightly (1.1%) at NPBS despite reductions in the absolute numbers of O+ distributions. Overall there was 2.6% decrease in the proportion of B+ and AB+ RBCs distributed and 13.6% absolute reduction in the number of these units distributed. CONCLUSION: Although overall RBC distributions have decreased over time, the proportion of O units has increased substantially.